2013
DOI: 10.1111/jcpp.12083
|View full text |Cite|
|
Sign up to set email alerts
|

Expanding the environment: gene × school‐level SES interaction on reading comprehension

Abstract: Background Influential work has explored the role of family socioeconomic status (SES) as an environmental moderator of genetic and environmental influences on cognitive outcomes. This work has provided evidence that socioeconomic circumstances differentially impact the heritability of cognitive abilities, generally supporting the bioecological model in that genetic influences are greater at higher levels of family SES. The present work expanded consideration of the environment, using school-level SES as a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 34 publications
(74 reference statements)
3
49
0
Order By: Relevance
“…It has been suggested that failures to find gene × SES effects are due to either sample selection -for instance twin pairs pre-selected for passing IQ criteria for admission to the US Armed Forces (Grant et al, 2010) or low sample size. This cannot explain, however, unpublished data in a representative sample of Florida children which failed to find gene × SES interaction (Soden-Hensler, 2012), although a significant gene interaction with a measure of school quality based on number of deprived students in the school was reported (Hart, Soden, Johnson, Schatschneider, & Taylor, 2013).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…It has been suggested that failures to find gene × SES effects are due to either sample selection -for instance twin pairs pre-selected for passing IQ criteria for admission to the US Armed Forces (Grant et al, 2010) or low sample size. This cannot explain, however, unpublished data in a representative sample of Florida children which failed to find gene × SES interaction (Soden-Hensler, 2012), although a significant gene interaction with a measure of school quality based on number of deprived students in the school was reported (Hart, Soden, Johnson, Schatschneider, & Taylor, 2013).…”
Section: Introductionmentioning
confidence: 76%
“…These data indicate that parental SES is not an obligate moderator of genetic variance in IQ. Along with other results (Hanscombe et al, 2012;Hart et al, 2013), the findings thus constrain and inform bioecological models which suggest a monotonic increase in heritability across varied environmental resources (Bronfenbrenner & Ceci, 1994).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, there are numerous studies that find no significant sex-effects in various measures of reading and math (e.g. Davis et al Behav Genet 2008;Hart et al 2013;Wadsworth and DeFries 2005).…”
Section: Sex Differencesmentioning
confidence: 97%
“…There are several types of rGE that play a substantial role in influencing environmental risk exposure, but their impact is best understood through the effects of parent and child behaviors in shaping and selecting environments [14]. Studies exploring the role of family social economic status (SES) as a moderator of genetic and environmental influences on general cognitive ability have provided evidence that socioeconomic circumstances differentially impact the heritability of cognitive abilities [15]. Furthermore, as SES is correlated with differences in life stress and family resources (e.g.…”
Section: Introductionmentioning
confidence: 99%